Grill&Gulasz, czyli o nazwach imprez kulinarnych - Przymuszała, Lidia; Świtała-Trybek, Dorota (Stylistyka, 2024)
Culinary tourism (part of a broader phenomenon called cultural tourism) has become extremely fashionable in recent years. It is closely related to culinary events organised on various occasions – accompanying other events or constituting the goal of a culinary trip in itself. An incentive to participate in them and a kind of trademark are the various names of these events, sometimes extremely original, testifying to the immense creativity of the organisers. The object of observation in this contribution are the names of culinary events belonging – according to Artur Gałkowski’s proposal – to ideational chrematonyms. The names of this subcategory of socioideonyms have not been sufficiently developed yet, so they have become the subject of research. Accordingly, the aim of this article is a formal and semantic analysis of these names, a discussion of the motivation behind the presented onyms, and an indication of their functions. The research basis for the observations made are 165 names of culinary events, organised periodically in the years 2019-2023 in three voivodeships: Silesia, Lower Silesia and Opole. The analysis of the material shows that multi-word constructions consisting of elements such as: a component identifying the project (e.g. festiwal [festival], święto [celebration], warsztaty [workshop]), specifying its nature (e.g. wodzionki [of Wodzionka soup], smaków [of flavours], maszketówi [of Silesian sweets]), locating event (e.g. w Lyskach [in Lyski], w Bagieńcu [in Bagieniec]) are very characteristic of this type of names. The basic naming model can be supplemented with various variant components. Onyms of this category, apart from their primary informative function, also play marketing, persuasive and promotional roles.